History of Economic sanctions: Key research questions (with some answers for 2022 sanctions against Russia) - Begović Boris (Anali Pravnog Fakulteta u Beogradu)
The paper proposes several key questions that should be unavoidable in the research on history of economic sanctions. Four key questions are identified. The first one is what the aim of the sanctions is; what are they supposed to achieve? The second question relates to the mechanisms of sanctions. The third question is, are sanctions effective, i.e. do they produce economic impact and what is its magnitude? The fourth question is, are sanctions efficient, i.e. has the aim been achieved? All these questions are further developed into several more specific questions. Crucial methodological obstacles to answering all these questions are identified and guidelines for overcoming them are provided. The answers to the proposed key questions should be only the starting point in research on history of economic sanctions. Some preliminary answers to these questions were given for the case of February 2022 sanctions against Russia, imposed after it invaded Ukraine.